Kaji Eksperimental Turbin Angin Hybrid Dengan Variasi Sudut Pitch Blade Propeler - Fauzi Syahryandi; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Hybrid turbine is a combination of two types of turbines into the one. The purpose of combining turbines is to improve the performance of each turbine. In this study, propeller turbine and venturi turbine are combined into the one. Energy ball wind turbine is placed in front of propeller turbine. The diameter used by propeller turbine is 200 cm with NREL S833 airfoil and venturi diameter of 50 cm. The number of propeller turbine consist of blades of 3 pieces and 5 venturi pieces. Then the pitch angle variation on the propeller turbine blade is 30º, 45º and 60º with a wind speed of 2.5 m/s to 5 m/s. From the result test show the addition of a large pitch angle reduce the power generated by the turbine, the addition of a venturi turbine to the propeller turbine can increase power at every pitch angle variation. The highest power is a produced by hybrid turbines with a pitch angle variation of 30º that is equal to 0.655 watts.Keywords : Propeller turbine, hybrid turbine, energy ball wind turbine